Địa lý kinh tế - xã hội châu Mỹ, châu Phi và châu Đại dương / Bùi Thị Hải Yến, Phạm Thị Ngọc Diệp, Nguyễn Yến Ngọc - Bùi,Thị Hải Yến ( chủ biên )
Cuốn sách cung cấp các tài liệu về đại lý kinh tế - xã hội châu Mỹ, châu Phi và châu Đại dương.